Biomarkers in Pancreatic Neuroendocrine Tumors - Theochari, Maria Serafeim; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
The aim of biomarkers is to identify patients most likely to benefit from a therapeutic strategy. Pancreatic neuroendocrine tumors are rare neoplasms that arise in the endocrine tissues of the pancreas. Pancreatic neuroendocrine tumors represent 3% of primary pancreatic neoplasms and their incidence has risen. The SMAD4 gene is located on chromosome 18q and someday the SMAD4 gene status may be useful for prognostic stratification and therapeutic decision. The cells respond to environmental signals by modulating the expressions of genes contained within the nucleus, when genes are activated are transcribed to generate messenger RNA (mRNA). The examination of multiple expressed genes and proteins provides more useful information for prognostication of individual tumors. Here we summarize and discuss findings presented at the 2014 ASCO Gastrointestinal Cancers Symposium. Anna Karpathakis et al. (Abstract #212) reported data about the role of DNA methylation in gastrointestinal neuroendocrine tumors. Christina Lynn Roland et al. (Abstract #250) looked the impact Of SMAD4 on oncologic outcomes. Bong Kynn Kang et al. (Abstract #251) investigated prognostic biomarker using microRNA array technology. Image: Sotiria Hospital, Athens, Greece: The Museum of Salvation